Rumen degradability in situ of maize grains of contrasting genotypes (Semiárida, 2018)
The rumen digestion of three maize hybrids with contrasting characteristics: flint (PROZEA 33), semi dent (AW 190 mg) and dent (CL 849 EXP), presented in the form of whole grains and three milling fractions, was evaluated. Each material was incubated in the rumens of 3 Hereford steers, fitted with rumen cannulaes, in nylon bags, for 3, 6, 9, 12, 24 and 48 hours for the three fractions, and 48 hours only for whole grain. The information obtained was fitted by an exponential equation with lag time, and the results subjected to analysis of variance and compared by test of Tukey. The highest effective degradability (ED) (p
Keywords: Grain; Maize; Milling; Flint; Dent; Degradability